Antibiotic prescribing knowledge: A brief survey of providers and staff at an ambulatory cancer center during Antibiotic Awareness Week 2019. Issue 1 (4th February 2022) - Gulleen, Elizabeth A.; Krantz, Elizabeth M.; Zier, Jacqlynn; Bhattacharyya, Pooja; Kates, Olivia; So, Lisa; Sweet, Ania; Yoke, Leah H.; Pergam, Steven A.; Liu, Catherine
Abstract: We surveyed healthcare professionals at a cancer center regarding their knowledge and perceptions of antibiotic use. Most knew the term "antimicrobial stewardship." Nurses and other staff were less likely than pharmacists or providers to answer knowledge-based questions correctly. Opportunities exist to improve antibiotic knowledge among cancer center staff.